Laporan Keberlanjutan dan Profitabilitas terhadap Return Saham dengan Nilai Perusahaan sebagai Variabel Moderasi - Tacfia Fitri Handayani; Tantina Haryati (Journal of Management and Bussines (JOMB), 2023)
This study aims to examine and analyze the effect of sustainability reports and profitability on stock returns, and test the company's value moderates sustainability and profitability reports on stock returns. This research method uses quantitative through financial data instruments. The research sample consisted of 32 Mining Companies listed on the IDX for the 2018-2021 period. The results showed, a) sustainability reports on stock returns have a value for path coefficient -0.071 (negative) and a P value of 0.842 (not significant); b) profitability on stock returns has a value for the path coefficient of 0.372 (positive) and a p value of 0.328 (not significant); c) company value mediating sustainability reports on stock returns has a path coefficient value of -0.915 (negative/weakening) and a p value of 0.175 (not significant); d) company value mediating profitability on stock returns has a path coefficient value of 0.754 (positive/strengthening) and a p value of 0.265 (not significant). In conclusion, sustainability reports, profitability do not affect stock returns and firm value does not moderate sustainability and profitability reports on stock returns. Keywords: Sustainability Report, Firm Value, Profitability, Stock Return